Hots Manifestation in English Summative Assessment - Achadiyah, Rachmawati; Muhammad Ulul Azmi (English Education:Journal of English Teaching and Research, 2023)
Higher-order thinking gains a positive role in language assessment since it is compulsory to be implemented in the teaching-learning and evaluation system of the latest curriculum. The implementation of HOTS in English tests assists students in practicing their analytical, critical, and problem-solving skills in real life. It is essential to know how the hots question is narrated in English summative assessment. Myriad research has examined the thinking level applied in English summative tests. However, there has been less previous evidence for portraying how the hots questions were being narrated. This study specifically employed a case study as a research design with content analysis as the technique to analyze the data. Three papers of the English summative test of the first, second, and third grades of junior high school became the source of the data. The result highlighted that the ninth-grade English summative test applied higher-order thinking in 72% of both multiple choice and essay. The thinking levels used are giving a solution, giving a recommendation, giving an opinion, making judgments, and interpreting. This study discovered how English teachers also, as the test designers, formulate hots questions in English summative tests.